Analisis Perilaku dan Prestasi Belajar Wirausaha Mahasiswa melalui Penerapan Project Based Learning bermuatan Technopreneurship - Niken Niken; Elfizon Elfizon (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
This study aims to find out whether or not entrepreneurial behavior and learning achievement in industrial electrical installation courses through the application of project-based learning models loaded with technopreneurship. And to find out there is an increase between entrepreneurial behavior and student learning achievement before applying project-based learning loaded technopreneurship and entrepreneurial behavior and learning achievement after applied project-based learning loaded technopreneurship at Padang State University. This research uses quantitative approaches with research methods. The instrument used is a questionnaire response of student entrepreneurial behavior to project-based learning and student value data to project-based learning. The subjects in this study were D4 students who took industrial electrical installation courses including grades 3 TEIB 1 and 3 TEIB 2 amounting to 30 people. Analysis of instrument data in this study using the help of SPSS 25.0.0 and Microsoft Exel programs. The results of this study show that: (1) Entrepreneurial behavior towards the application of project-based learning loaded technopreneurship that has been applied is emerging and effective to improve entrepreneurial behavior from the results of research that shows in the high category (2) Student learning achievement towards the application of project-based learning loaded with technopreneurship that has been applied is also emerging and effective to improve student entrepreneurial learning achievement from research results that show a high category.